UPAYA KEMAMPUAN MENYIMAK ANAK DENGAN METODE BERCERITA MENGGUNAKAN PAPAN FLANEL DI SPS MEKAR KARYA IV BABAKANBARU - Entin (Pondok Pesantren Baitul Qur`an Sambas, 2024)
This research aims to improve children's listening skills using the storytelling method using flannel board media for children in Group A SPS Mekar Kary IV Babakan Baru, Ciracap District, Sukabumi Regency. This research is Classroom Action Research. The subjects of this research were children from Group A SPS Mekar Kary IV Babakan Baru. The object of research is listening ability. The method used in collecting data is observation and documentation taken during the learning process. The analysis technique used in this research is quantitative descriptive. This research was carried out in 2 cycles, each cycle lasting 2 meetings. The results of the research show that the listening ability of Group A SPS Mekar Kary IV Babakan Baru children can be improved. The results of pre-action observations showed that there were no children who had the criteria for developing very well or who got a percentage of 76-100%. After the actions in Cycle I, the average ability of children increased to 66% with the criteria of developing according to expectations (BSH), and in Cycle II the average ability of children increased to 82.5% with the criteria of developing very well (BSB).